High‐sensitivity sulfur isotopic measurements for Antarctic ice core analyses. (6th November 2018) - Takahashi, Kazuya; Nakai, Yoichi; Motizuki, Yuko; Ino, Toshiyuki; Ito, Shigeru; Ohkubo, Satoru B.; Minami, Takeshi; Takaku, Yuichi; Yamaguchi, Yoshitaka; Tanaka, Miho; Motoyama, Hideaki
Abstract : Rationale: Sulfur is widely distributed in nature, and sulfur isotopic measurements have been applied to elucidate the origin and transport of sulfuric compounds in the lithosphere, biosphere, and atmosphere. Analyses of samples containing small amounts of sulfur, such as the Antarctic ice core samples analyzed herein, require a high‐sensitivity analytical method. Methods: We developed a high‐sensitivity sulfur isotopic ratio (δ 34 S value) analytical system equipped with an elemental analyzer, a cryo‐flow device, and an isotope ratio mass spectrometer, and established a measurement and calibration procedure. Results: Using this system, we precisely measured the δ 34 S values of samples containing 5–40 nmol sulfate. Test runs were performed on samples from the Antarctic shallow ice core DF01, and the data obtained were consistent with those obtained by previous studies that reported δ 34 S values for Antarctic snow and ice samples of more than 200 g (containing more than 150 nmol sulfate). Among the analyzed samples, one showed a peak sulfate concentration in its depth profile that is considered to have resulted from a large volcanic eruption. The δ 34 S value obtained at that depth in the sample was distinct from values at other depths and consistent with reported values for volcanic sulfates. Conclusions: The analytical system developed herein is a powerful tool for trace sulfur isotopic analyses. The results obtained from the DF01 ice core samples are the first step towards elucidating high‐time‐resolution (less than 1 year) paleo‐environmental changes by sulfur isotopic analyses.